Islamic Banks: Study of Financial Literacy, Digital Marketing, Accessibility, Age, and Education - Dhidhin Noer Ady Rahmanto; Irsyad Syaiful Muhammad; Feni Nurwiyanti; Al Haq Kamal; Ageng Asmara Sani (Universitas Pembangunan Nasional Veteran Jakarta, 2023)
The emergence of the Islamic banking Industry in Indonesia up to now has not escaped from challenges and problems, among the main ones is how Islamic banks are leading the market share by increasing customer interest in using Islamic banking services. Quantitative methods were used in this research with a sample of 100 respondents of Islamic bank customers who lived in a special region of Yogyakarta which was selected by using a purposive sampling approach, and multiple linear regression by using SMART PLS 2.0. applied as the tools of analysis. The result shows that financial literacy does not affect the interest in becoming Islamic customers. Meanwhile, digital marketing and accessibility do affect the interest in becoming Islamic bank customers. Then, age and education as moderating variables are not able to moderate financial literacy, digital marketing, on interest in becoming Islamic bank customers. The practical implications of this research suggest that marketers can make more informed decisions, such as intensifying promotional efforts on digital platforms and enhancing customer accessibility. Additionally, this study recommends further research to address the limitations by including cybersecurity perceptions as a moderating variable. By doing so, the research will be able to provide a more comprehensive understanding of the subject matter.